The impact of employee job satisfaction on the relationship between HRM practices and organizational commitment: a conceptual study on RMG sector of Bangladesh - Ulfy, Mohammad Arije; Haque, A. K. M. Ahasanul (Publication Unit, Faculty Economics and Business, Universitas Gadjah Mada, 2020)
“Job satisfaction” is a pleasant or encouraging state of expression which is consequential from the valuation of one’s “organizational commitment”. The gladder the employee, the higher is the mindset of “job satisfaction”. It is presumed that “quality of work-life” and “compensation benefits” enhances “job satisfaction” which in reappearance increases employee’s “organizational commitment”. This research determines to inspect the underlying relations among HRM practices and organizational commitment on job satisfaction in the RMG sector in Bangladesh. This study will explore the impact of employee job satisfaction on the relationship between organizational commitment and HR practices. An experimental investigation will be presented in what manner HRM determinant impact organizational commitment and job satisfaction for the RMG sector’s employee in Bangladeshi circumstance. Study data will attain from the RMG sector, at least 385 responses will be analysed by using SEM (Structural Equation Modelling). Data will accumulate through a detailed structured questionnaire from the respondents. Simple random sampling method will be used to procure the respondents.